FAKTOR–FAKTOR YANG BERPENGARUH SIGNIFIKAN TERHADAP INDEKS PEMBANGUNAN MANUSIA DI PROVINSI PAPUA - KADRI, INA AZIZAH; SUSILAWATI, MADE; SARI, KARTIKA (E-Jurnal Matematika; Vol 9 No 1 (2020), 2020)
Geographically weighted regression (GWR) analysis is one of an analysis to resolve the problem with data contains effect of spatial heterogenity. One of the problems which considers spatial heterogeneity is human development index (HDI) . HDI is an indicator that used to measure success in building quality of human life . One of the provinces with the lowest HDI in Indonesia is Papua . The purpose of this research  is to know the contribution of each HDI factors in Papua using GWR method . The weighting function used is adaptive gaussian kernel. The results of this research showed HDI’s dominant factors in Papua, expected years of schooling and mean years of schooling.